A novel HSF4 gene mutation (p.R405X) causing autosomal recessive congenital cataracts in a large consanguineous family from Pakistan - Cheema Abdul; Kakar Naseebullah; Goebel Ingrid; Sajjad Naheed; Kubisch Christian; Ahmad Jamil (BMC, 2008)
Abstract Background Hereditary cataracts are most frequently inherited as autosomal dominant traits, but can also be inherited in an autosomal recessive or X-linked fashion. To date, 12 loci for autosomal recessive cataracts have been mapped including a locus on chromosome 16q22 containing the disease-causing gene HSF4 (Genbank accession number NM_001040667). Here, we describe a family from Pakistan with the first nonsense mutation in HSF4 thus expanding the mutational spectrum of this heat shock transcription factor gene. Methods A large consanguineous Pakistani family with autosomal recessive cataracts was collected from Quetta. Genetic linkage analysis was performed for the common known autosomal recessive cataracts loci and linkage to a locus containing HSF4 (OMIM 602438) was found. All exons and adjacent splice sites of the heat shock transcription factor 4 gene (HSF4) were sequenced. A mutation-specific restriction enzyme digest (HphI) was performed for all family members and unrelated controls. Results The disease phenotype perfectly co-segregated with markers flanking the known cataract gene HSF4, whereas other autosomal recessive loci were excluded. A maximum two-point LOD score with a Zmax = 5.6 at θ = 0 was obtained for D16S421. Direct sequencing of HSF4 revealed the nucleotide exchange c.1213C > T in this family predicting an arginine to stop codon exchange (p.R405X). Conclusion We identified the first nonsense mutation (p.R405X) in exon 11 of HSF4 in a large consanguineous Pakistani family with autosomal recessive cataract.